Introductory Head & Neck Radiology for Preclinical Learners - Frank Reilly; Mahesh Kamsala; Allison Davis; Jeffrey Altemus; Saritha Reddy (Association of American Medical Colleges, 2008)
Abstract Introduction This is an interactive tutorial that serves as an introduction to head and neck x-rays and cross-sections for first-year medical and dental students. A series of digitized radiographs were converted into Adobe Flash for online distribution. The objective for creating the courseware was to stimulate active self-directed learning. The rationale was to integrate introductory radiographic anatomy into a structured format that is readily accessible for local and distance learning and self-assessment. Methods Active learning was achieved by creating five radiology tutorial units that target content areas dealing with standard and cross-sectional radiographic anatomy and arterial angiography. The courseware provides beginners with introductory imaging that is critical to the interpretation of standard X-rays and CT and MRI scans. It complements didactic and practical activities of preclinical health care professionals enrolled in human structure. Results Since implementation of the courseware in 2001, 8% more students score correct answers on exam questions. Last year learners scored at the 77th percentile on the NBME anatomy subject examination. Discussion Organizing content into discrete tutorials is highly effective in teaching learners a large volume of information without overwhelming them. Exposing preclinical students to introductory head and neck x-rays and cross-sections provide learners with a glimpse into the comprehensive evaluation of more contemporary imaging techniques like CT, MRI, and PET scans. Framing content in a clinically relevant manner not only serves to solidify what students have learned in their courses, but also creates confidence by demonstrating how they will approach patient problems in their clinical years. These observations are supported by recent improvements in learner performance on block and subject shelf exams.